THE EFFECTIVENESS NUMBER OF BAFFLE BLOCKS TO REDUCE ENERGY IN TUKUTAHA TRANSITION CHANNELS - Agustina Nababan; Nadjadji Anwar; Wasis Wardoyo (Journal of Civil Engineering, 2021)
One of the causes of damage to the weir structure is scouring. Scouring may occur along the weir channel. Scouring occurs due to the high flow velocity and high specific energy. One of the methods used to reduce specific velocity and energy is by installing baffle blocks in parts that have high-velocity and energy. The addition of baffle blocks is carried out at a place that has a high-velocity, namely the transition channel. To see the effect of baffle block variation on velocity and energy, a study was conducted. The study was conducted with four baffle block type models. The type 0 model is a baffle block installation pattern based on the initial design. Type 1 model is designed based on the planning of The Colorado State University (CSU) rigid boundary basin. Type 2 model is designed by reducing the number of baffle blocks from the initial design of 102 baffles to as many as 75 baffles. while the 3 channel type model transitions without baffle blocks. Based on the analysis of % energy loss in the transition channel, the type 0 model produces the largest energy loss. The type 0 model at maximum discharge has a % energy loss 10.821% greater than the type 1 model, 14.889% greater than the type 2 model and 33.02 % greater than the type 3 model.